MEMBANGUN PENDIDIKAN KARAKTER MELALUI PENDIDIKAN BAHASA DI KELUARGA - Defina, Defina (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA, 2017)
The general purpose of this paper was to describe the character education in families through language. The specific purposes were 1) the definition of character; 2) the definition of education; 3) character education; 4) family definition; 5) how to instill character education through language education in the family. Character is a collection of good behavior of a human. Child education in the family is done through parenting by the parents. The education of characters in the family through the language can be done with the selection of diction in communication. The elderly can choose the right diction in accordance with the purpose of communication. Dies selected by parents will vary according to emotion. The use of language is started from early childhood until he becomes an adult.